PENGARUH PENERAPAN MANAJEMEN MUTU TERPADU DAN KOMITMEN ORGANISASI TERHADAP EFEKTIVITAS IMPLEMENTASI TEACHING FACTORY DI SEKOLAH MENENGAH KEJURUAN (SMK) SE-KOTA BANDAR LAMPUNG - Widianti, Windi; Dermawan, Oki; Rinaldi, Achi (STKIP Pesisir Selatan, 2025)
This study aims to analyze the influence of Total Quality Management (TQM) implementation and Organizational Commitment on the effectiveness of Teaching Factory implementation in Vocational High Schools (SMK) across Bandar Lampung City. The research employed a quantitative method with a sample of 75 respondents. Data were collected using standardized instruments and analyzed using SPSS 25 through descriptive statistics and multiple linear regression tests. The findings indicate that the implementation of Total Quality Management is in the good category, with a mean score of 15.61 and a standard deviation of 1.793, and the data distribution shows a tendency toward normality. The results also reveal that Organizational Commitment has a positive and significant effect on Teaching Factory effectiveness, with a significance value of 0.01, where the normative commitment dimension shows the highest correlation at 0.924. Furthermore, the multiple regression analysis demonstrates that Total Quality Management and Organizational Commitment simultaneously have a positive and significant effect on the effectiveness of Teaching Factory implementation, as shown by an R value of 0.690 and an R Square value of 0.515, indicating that both variables collectively explain 51.5% of the variance in Teaching Factory effectiveness.